2020
DOI: 10.7717/peerj.10454
|View full text |Cite
|
Sign up to set email alerts
|

Supraspecific units in correlative niche modeling improves the prediction of geographic potential of biological invasions

Abstract: Background Biological invasions rank among the most significant threats to biodiversity and ecosystems. Correlative ecological niche modeling is among the most frequently used tools with which to estimate potential distributions of invasive species. However, when areas accessible to the species across its native distribution do not represent the full spectrum of environmental conditions that the species can tolerate, correlative studies often underestimate fundamental niches. Methods Here, we explore the uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 61 publications
(67 reference statements)
0
17
0
Order By: Relevance
“…Those studies that have reported their choice of parameter have used values of k = 0.95 ( Soberón, Peterson & Osorio-Olvera, 2018 ; Altamiranda-Saavedra et al, 2020 ; Castaño-Quintero et al, 2020 ), k = 0.975 ( Osorio-Olvera et al, 2020 ; Castaño-Quintero et al, 2020 ), and k = 0.99 ( Yañez-Arenas et al, 2018 ). These seem to be sensible choices based on the virtual experiments conducted here, as in comparison to the sample means and variance-covariance method, when k = 0.95 the MCD and MVE methods will not be too negatively affected by small sample sizes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those studies that have reported their choice of parameter have used values of k = 0.95 ( Soberón, Peterson & Osorio-Olvera, 2018 ; Altamiranda-Saavedra et al, 2020 ; Castaño-Quintero et al, 2020 ), k = 0.975 ( Osorio-Olvera et al, 2020 ; Castaño-Quintero et al, 2020 ), and k = 0.99 ( Yañez-Arenas et al, 2018 ). These seem to be sensible choices based on the virtual experiments conducted here, as in comparison to the sample means and variance-covariance method, when k = 0.95 the MCD and MVE methods will not be too negatively affected by small sample sizes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 ), we can see that both the MCD and MVE methods ignore the apparent outlier and produce measures of multivariate location and scatter that are focussed on where the data are more concentrated. Given the robustness of MCD and MVE methods to outliers resulting from errors in natural history observation data, it is perhaps no surprise that both methods have been adopted recently for ecological niche modelling ( Norris, Jackson & Betancourt, 2006 ; Liu, White & Newell, 2018 ; Soberón, Peterson & Osorio-Olvera, 2018 ; Yañez-Arenas et al, 2018 ; Qiao et al, 2019 ; Altamiranda-Saavedra et al, 2020 ; Osorio-Olvera et al, 2020 ; Castaño-Quintero et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been assessed under different taxonomic groups that explored the contribution of using supraspecific modelling units in niche construction showing that those modelling units improved the predictive ability of the ecological niche models. Specifically, by adding the occurrences of closer taxa reduced the omission rates considerably [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…2019; Castaño‐Quintero et al . 2020), particularly when working with fossil taxa (e.g. Waterson et al .…”
Section: Methodsmentioning
confidence: 99%